The Impacts of Ecosystem Hypertrophication and Climate Changes on Thrive of the Jellyfish in Shatt Al-Basrah Canal - Ali Bassal Mahmood; Imad J. M. Al-Shawi; Hazem A. Al-Sayab; Sejad K. Jasib; Zuhair A. Abdulnabi; Nadia K. Muhsen; Yosra J. Alewi (Marine Science Department Diponegoro University, 2019)
The present study (i.e. the first study in Iraqi waters) identified the causes of reproduction and excessive growth of the jellyfish, which locally known as thagolol, of the type (Catostylus perezi) in the region of Shatt Al-Basrah canal - west of Basrah city. The reproduction and excessive growth of jellyfish occurs in many estuaries and coastal areas in the world, which is a recurring global problem in the context of climate change. The conducted study was included measurements of dissolved oxygen, electrical conductivity, total dissolved solids, pH, temperature, nitrates, phosphate, quality and quantity of phytoplankton during the dominant of :the northwest winds; the neap tide and during a full tidal periods in October of 2018 and March of 2019. The results showed that there were thrive of jellyfish by huge numbers in Shatt Al-Basrah canal. The physical; chemical and biological causes (i.e., the local causes), were identified, namely: (1) salinity, (2) water column temperature stratification in the context of climate change, (3) an excessive increase in the concentrations of nitrate and phosphate, (4) abundance of phytoplankton (i.e. dinoflagellate), including Protoperidinium sp. and Alexandrium sp.; and (5) overfishing. Hence, the absence of any of these factors will lead to the absence of this type of jellyfish.